2012
DOI: 10.1093/jpepsy/jss067
|View full text |Cite
|
Sign up to set email alerts
|

Family and Youth Factors Associated With Health Beliefs and Health Outcomes in Youth With Type 1 Diabetes

Abstract: Understanding the mechanisms by which family organization is associated with metabolic control provides insight into possible avenues of prevention/intervention for better diabetes management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 38 publications
(55 reference statements)
1
33
0
Order By: Relevance
“…Greater self-efficacy helps youth exert sufficient effort to master and maintain diabetes care behaviors. Moreover, higher self-efficacy mediates the relation between having more diabetes responsibility and demonstrating better treatment adherence (Ott, Greening, Palardy, Holderby, & De-Bell, 2000), and between an organized, supportive family environment and in-range glycemic control (Herge et al, 2012). …”
Section: Theories Of Behavioral Interventionsmentioning
confidence: 99%
“…Greater self-efficacy helps youth exert sufficient effort to master and maintain diabetes care behaviors. Moreover, higher self-efficacy mediates the relation between having more diabetes responsibility and demonstrating better treatment adherence (Ott, Greening, Palardy, Holderby, & De-Bell, 2000), and between an organized, supportive family environment and in-range glycemic control (Herge et al, 2012). …”
Section: Theories Of Behavioral Interventionsmentioning
confidence: 99%
“…Indeed, parents who report greater parenting stress and depressive symptoms tend to also report lower diabetes self-efficacy (Streisand et al, 2008; Streisand et al, 2005). There are mixed results regarding the impact of diabetes self-efficacy on diabetes management behaviors and glycemic control, with one study finding that maternal and youth diabetes self-efficacy were related to better glycemic control in adolescents due to a significant positive correlation with better disease management and another finding no relationship between self-efficacy and glycemic control (Herge et al, 2012; Marvicsin, 2008). Although additional research is needed to understand these associations, it is likely that the relationship among hypoglycemia worry, diabetes self-efficacy, and parent T1D management behaviors are intertwined.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence supports relationships within the framework and suggests the potential role of self-management as a mediator between family functioning and adaptation. For example, researchers have demonstrated that the relationship between family conflict/cohesion and glycemic control is mediated by self-management (Herge et al, 2012; Hilliard, Guilfoyle, Dolan, & Hood, 2011; Hilliard et al, 2013); and self-management has been shown to be a mediator between youth depressive symptoms and glycemic control (McGrady, Laffel, Drotar, Repaske, & Hood, 2009). To date, there is no research exploring mediators between family functioning or depressive symptoms and quality of life in adolescents with type 1 diabetes.…”
mentioning
confidence: 99%